2017
DOI: 10.1161/strokeaha.116.014889
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Thrombolysis in Unknown-Onset Stroke

Abstract: Background and Purpose-Stroke patients with unknown onset (UKO) are excluded from thrombolytic therapy. We aim to study the safety and efficacy of intravenous alteplase in ischemic stroke patients with UKO of symptoms compared with those treated within 4.5 hours in a large cohort. Methods-Data were analyzed from 47 237 patients with acute ischemic stroke receiving intravenous tissue-type plasminogen activator in hospitals participating in the Safe Implementation of Treatment in Stroke-International Stroke Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They are usually considered as a contraindication for intravenous thrombolysis for the uncertain symptom onset. There is an increasing attention to determine the potential role of thrombolytic therapy for patients in this situation [3234]. A trial in 2009 [15] indicated that thrombolysis-treated WUS had higher rates of excellent and favorable outcome but higher mortality than those receiving conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually considered as a contraindication for intravenous thrombolysis for the uncertain symptom onset. There is an increasing attention to determine the potential role of thrombolytic therapy for patients in this situation [3234]. A trial in 2009 [15] indicated that thrombolysis-treated WUS had higher rates of excellent and favorable outcome but higher mortality than those receiving conservative treatment.…”
Section: Discussionmentioning
confidence: 99%